Phenotyping Study of Cyclophosphamide 4-Hydroxylation in Malay Cancer Patients - Fityatal Hasanah YI; Harahap Y; Purwanto DJ (Dove Medical Press, 2021)
Yesi Ihdina Fityatal Hasanah,1 Yahdiana Harahap,1,2 Denni Joko Purwanto3 1Bioavailability and Bioequivalence Laboratory, Faculty of Pharmacy, Universitas Indonesia, Depok, Indonesia; 2Indonesia Defense University, Bogor 16810, West Java, Indonesia; 3Functional Medical Staff of Surgical Oncology, Dharmais Cancer Hospital, Jakarta, IndonesiaCorrespondence: Yahdiana Harahap Griya Depok Asri Blok G3 No. 1, Depok City, West Java 16411, IndonesiaEmail yahdiana@farmasi.ui.ac.idBackground: Cyclophosphamide (CP) is an anticancer alkylating group (nitrogen mustard) and a prodrug that will be metabolized to form its active metabolite, 4-hydroxycyclophosphamide (4-OHCP). The various enzymes involved in its bioactivation can cause a wide range of CP expression and activity among patients and ultimately affect the metabolism, efficacy and toxicity of this drug. The effectiveness of CP therapy can be determined by 4-OHCP level in dried blood spot (DBS).Aim: The purpose of this study was to conduct the phenotyping of CP 4-hydroxylation rate in Malay cancer patients.Methodology: Phenotyping study of CP 4-hydroxylation rate to 40 subjects of Malay cancer patients was done based on the value of its bioactivity ratio (4-OHCP to CP levels).Results: The result shown the cyclophosphamide 4-hydroxylation rate of 80% (n=32) subjects as ultrarapid metabolizer (UM) and 20% (n=8) as poor metabolizer (PM).Conclusion: Phenotyping study of CP 4-hydroxylation in Malay cancer patients can be conducted by quantifying CP bioactivity ratio (4-OHCP to CP level) in dried blood spot. In majority of Malay cancer patients, cyclophosphamide would be bioactivated through 4-hydroxylation in hepar rapidly as indicated by the high value of the bioactivity ratio or the increased CP clearance and 4-OHCP level.Keywords: 4-hydroxycyclophosphamide, 4-OHCP, 4-hydroxylation rate, cyclophosphamide, CP, dried blood spots, DBS, Malay ethnicity